Household Financial Planning Education In Duyu Urban Village, Palu City - Abdul Jalil; Irham Pakkawaru; Moh. Syafa’at; Auriza Mitsaly (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Datokarama Palu, 2023)
Poor financial management can create chaos in the financial life of an individual or household. Excessive debt, financial crisis, mental stress, and limited investment in education and health are possible outcomes. The inability to achieve financial goals is a serious consequence. Therefore, wise financial management practices are essential to maintain financial stability and well-being in the long run. This activity aims to provide socialization and education in household financial management. The activity was carried out in Duyu's residence with 50 participants. The method used was a form of presentation and discussion with participants. The output of the activity is increasing community understanding of household financial management that can be implemented in realizing smart and effective households.